POTENSI RIZOBAKTERI YANG DIISOLASI DARI RIZOSFER TANAMAN LEGUMINOSAE UNTUK MENGENDALIKAN JAMUR Sclerotium rolfsii PENYEBAB PENYAKIT REBAH KECAMBAH PADA TANAMAN KEDELAI - Mahartha, Komang Adi; Suprapta, Dewa Ngurah; Wirya, Gusti Ngurah Alit Susanta (Journal of Agricultural Science and Biotechnology, 2017)
Damping off disease caused by Sclerotium rolfsii is an important disease of soybean, because soybean plant will die after attacked by pathogen. This pathogen can survive for a long time in the soil by sclerotia form. Some of rhizobacteria isolated from the rhizospheres of Leguminosae plants were known could control soil-borne pathogens. This study aims to test rhizobacteria isolated from the rhizosphere of Leguminosae plants that able to suppress the growth of S. rolfsii. Total of 11 isolates of 112 isolates rhizobacteria that could be isolated from Leguminosae plants had antifungal activity against S. rolfsii. Inhibition test of 11 isolates of rhizobacteria against S. rolfsii showed that three isolates had the highest ability to inhibit the growth of S. rolfsii namely isolates KtD1, KtD6, and KtB3. This result suggested that three isolates of rhizobacteria tested in this study can be further developed as bio-control agent to reduce the development of damping off disease on soybean.